Europe takes bite out of Microsoft. - Blau, J. (IEEE spectrum)
In April 2004 the European Union took steps to curb Microsoft's control of the computer software market by imposing tough sanctions aimed at its treasured "bundling" strategy and crafted to influence its future behavior in the market.